A violência de gênero na jurisprudência da Corte Interamericana de Direitos Humanos: Um estudo do caso González e Outras (“Campo Algodoeiro”) vs. México - Libardi, Brisa (Language and Law / Linguagem e Direito, 2022)
This paper sets out to discover how the Inter-American Court of Human Rights (IACHR) interprets gender violence in its jurisprudence, and whether this interpretation is consistent with an evolving interpretation of human rights and current discussions about gender violence. The article analyzes the Case of “González and others vs. Mexico” and the rationale decidendi of the case, using as a theoretical basis previous publications. We conclude that the IACHR current in its analysis of gender violence, gave special emphasis to crimes characterized as feminicide.